Epidemiology, Clinical Features, and Outcome in a Cohort of Adolescents With Cerebral Venous Thrombosis. (9th November 2021) - Devianne, Julia; Legris, Nicolas; Crassard, Isabelle; Bellesme, Celine; Bejot, Yannick; Guidoux, Celine; Pico, Fernando; Germanaud, David; Obadia, Michael; Rodriguez, Diana; Tuppin, Philippe; Kossorotoff, Manoelle; et al.
Abstract : Background and Objectives: We aimed to analyze the epidemiologic, clinical, and paraclinical features of adolescents with cerebral venous thrombosis (CVT) and its therapeutic management and outcome. Methods: This multicenter retrospective cohort included patients 10 to 18 years of age hospitalized for a first episode of CVT in 2 French regions between 1999 and 2019. The number of cases was compared to the number recorded by the French health insurance system. The CVT registry of the Lariboisière hospital allowed comparisons with adults. Results: One hundred two patients were included (52.9% female; median age 15.1 years). Estimated incidence was 0.37 to 0.38 per 100, 000 adolescents per year; 45.5% of patients presented with focal deficits or seizures or in a coma. Male patients were younger than female patients (14.2 vs 15.6 years; p < 0.01) and more often admitted to intensive care (52.1% vs 24.1%; p = 0.0, 035). The lateral sinus was the most common CVT location (72.3%), and 29.4% of adolescents had associated venous infarction or hematoma. Most patients (94.1%) received anticoagulation. Treatment also included an endovascular procedure (2.9%), decompressive craniectomy (4.9%), and CSF shunt (6.9%). The most frequently identified CVT-associated condition was local infection in male (18.6%) and systemic disease in female (14.8%; p < 0.001) patients. The proportion of CVTs in adolescents without an identified associated condition or risk factor was low (1.9% vs 11.4% in adults; p < 0.002). Adverse outcome at 1 year was more frequent than in adults (33.3% vs 11.8%; p = 0.0, 001). Discussion: CVT in adolescents is rare and complex with specific epidemiology, including differences in clinical presentation and associated conditions between sexes, and more severe outcomes than in adults. Careful specialized management and follow-up are therefore recommended.